Perylenetetracarboxylic diimide as a high-rate anode for potassium-ion batteries. Issue 42 (11th October 2019) - Bai, Yunfei; Fu, Wenbin; Chen, Wenhao; Chen, Zhichun; Pan, Xiaojun; Lv, Xiaoxia; Wu, Jincai; Pan, Xiaobo
Abstract : Benefitting from large space and semiconductor properties of PTCDI, a PTCDI electrode was constructed for PIBs. The electrode displays an excellent performance in optimized electrolytes which can be attributed to fast electron and ion transport kinetics. Abstract : Organic compounds are appealing electrode materials for potassium-ion batteries (PIBs) owing to their economical and eco-friendly nature. Here, we report an important organic semiconductor, 3, 4, 9, 10-perylenetetracarboxylic diimide (PTCDI), as a high-rate anode for PIBs. The PTCDI electrode is found to deliver a high average specific capacity of 310 mA h g −1 at 0.5 A g −1 and a remarkable rate performance (in the range from 0.5 to 5.0 A g −1 ), which can be attributed to the fast K ion diffusion (up to ∼10 −8 cm 2 s −1 ) and low charge-transfer resistance (93 ohm). The proposed six-electron storage mechanism for the PTCDI electrode during the discharge/charge process has been revealed by ex situ infrared (IR) spectroscopy and ex situ X-ray diffraction (XRD), as well as density functional theory (DFT) calculations. This study could pave the way for developing advanced PIB anodes with low cost and high performance.